KARAKTERISTIK TERMAL BRIKET ARANG SERBUK GERGAJI KAYU MERANTI - Patabang, Daud (Jurnal MEKANIKAL, 2013)
The aim of this research isÂ to find out of thermal characteristic of meranti wood dust briquette, that consist of High heating value (HHV), contents of Moisture (M),Ash (A),Volatile Matters (VM),Fixed Carbon (FC), combustion efficiency and emission gas product of combustions are ;carbon monoxides CO and Carbon dioxides CO2. This investigation is used experiment method to make char briquette of meranti wood dust and mixed with 10% of boil water, 5% of clay, 7% of tapioca and pressing force 2.5 Mpa. The result of investigations are; HHV 5731.10 kcal/kg. Ash 3.97%, Mouisture 1.72%, Volatile Matters 29.19%, Fixed Carbon 65.90 %, combustions efficiency 70.76% and emission gas product of combustions are CO 0.33% and CO2 1.36%, both of them are safe of human being according to WHO Standard.